Gene Therapy - Principles and Challenges 2015
DOI: 10.5772/61988
|View full text |Cite
|
Sign up to set email alerts
|

AAV Biology, Infectivity and Therapeutic Use from Bench to Clinic

Abstract: Adeno-associated virus (AAV) has been isolated from numerous vertebrate species since 1966. Besides its wide and promiscuous tropism, AAV infection does not result in considerable toxicity or pathogenicity and is capable of achieving adequate and long-term levels of gene transfer, especially following generation of the AAV recombinant variant: rAAV. Due to these properties, rAAV has gained special attention as a viral vector for gene therapy in the last decade. Currently, there are 130 clinical trials taking p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 66 publications
(74 reference statements)
1
20
0
1
Order By: Relevance
“…Previous studies have shown that infection by different AAV serotypes is mediated by a variety of cell surface receptors (for review see 34 ). Specifically, cell surface N-linked sialic acid has been proposed as the primary receptor for AAV1 and AAV6 to infect and transduce cells.…”
Section: Aav Serotype Infection Is Mediated By Different Receptors Onmentioning
confidence: 99%
“…Previous studies have shown that infection by different AAV serotypes is mediated by a variety of cell surface receptors (for review see 34 ). Specifically, cell surface N-linked sialic acid has been proposed as the primary receptor for AAV1 and AAV6 to infect and transduce cells.…”
Section: Aav Serotype Infection Is Mediated By Different Receptors Onmentioning
confidence: 99%
“…All AAV serotypes share at least 50% sequence homology. However, serotype AAV5 has the most divergent amino acid capsid sequence, and AAV4 also shows a considerable degree of divergence [50]. Surprisingly, this sequence diversity between serotypes is not scattered but primarily located in the looped out domains of the capsid protein [51].…”
Section: Aav Serotypes and Tissue Tropismmentioning
confidence: 99%
“…Close homology to all serotypes except AAV 4, 5, 11, and 12 [50] Low transduction efficiency [52] Liver, heart, muscle [52] AAV3 Low transduction efficiency Slow in targeting the tissues [52] Heart, liver [52] AAV4…”
Section: Aav1mentioning
confidence: 99%
See 2 more Smart Citations